Predation risk drives the expression of mobbing across bird species. (9th September 2017) - Cunha, Filipe Cristovão Ribeiro da; Fontenelle, Julio Cesar Rodrigues; Griesser, Michael
Abstract : Mobbing is a costly behavior in which prey face a potential predator. Ecological and social traits should influence its expression across species, but their influence on mobbing remains unknown. We exposed birds to 2 owl models that pose different risks. In particular, species that have optimal-prey body size, forage in a safer niche, and form flocks engaged in mobbing. Also, birds adjusted their behavior according to the risk posed by the predator. Abstract: Many species approach predators to harass and drive them away, even though mobbing a predator can be deadly. However, not all species display this behavior, and those that do can exhibit different behaviors while mobbing different predators. Here we experimentally assessed the role of social and ecological traits on the expression of mobbing behavior in a bird community in SE Brazil ( n = 157 species). We exposed birds to models of two morphologically similar diurnal owls that pose different risks, and assessed which species engaged in mobbing. Among those that mobbed, we evaluated how they adjusted their mobbing behavior depending on the predator type. We tested the hypothesis that only species that are at risk and can afford to mob engage in this antipredator behavior. We found that species that engaged in mobbing are in the body mass range of potential prey, forage in the understory or in the canopy, and form flocks. A species' social system did not influence its mobbing behavior. Furthermore, species that engaged in mobbing formed larger mobbing assemblages when facing a high-risk predator, but mobbed more intensely when facing a low-risk predator. Our findings support our predictions, namely that the expression of mobbing is limited by its costs.